2011
DOI: 10.1111/j.1467-7660.2011.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Protection and Class Relations: Evidence from Scheduled Caste Women's Associations in Rural South India

Abstract: This article argues that the labouring class poor are best able to access social protection when they have sufficient economic autonomy from their village's dominant class to allow them to act politically. To this end, the article analyses the capacity of associations of scheduled caste female labourers in rural Karnataka (south India) to access social protection through collective action. It identifies links between modifications of the material conditions of the labouring class, their capacity to take politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…There was almost complete agreement between the two researcher assessors. In two cases associated with consideration of ethical issues and one case associated with the relationship between the researcher and the participants, one researcher felt that she could not tell whether a criterion was met, whereas the other researcher was able to identify the information to answer the criteria (Pattenden, 2011;Ramachandar & Pelto, 2009;Kumari, 2011). 5 Details of the quality appraisal assessment criteria are in Appendix 5.…”
Section: Quality Of Qualitative Studiesmentioning
confidence: 99%
“…There was almost complete agreement between the two researcher assessors. In two cases associated with consideration of ethical issues and one case associated with the relationship between the researcher and the participants, one researcher felt that she could not tell whether a criterion was met, whereas the other researcher was able to identify the information to answer the criteria (Pattenden, 2011;Ramachandar & Pelto, 2009;Kumari, 2011). 5 Details of the quality appraisal assessment criteria are in Appendix 5.…”
Section: Quality Of Qualitative Studiesmentioning
confidence: 99%
“…In contrast, in the similarly remote village of Shiva Camp, NREGS work had been non‐existent from 2007, when GP officials had taken labourers' job cards, until July 2014 (when fieldwork was last conducted). This reflected the broader sociopolitical dynamics in that village: access to non‐agricultural labour markets is lower, control over labour greater, the GP office more remote and the JMS considerably weaker (see Pattenden ). Critically, this was an almost wholly canal‐irrigated village, and farmers had a greater need for labour power than in the drier village of Jagalwara.…”
Section: Class Conflict In Raichurmentioning
confidence: 99%
“…Although the level of NREGS works was lower, the level of appropriation of NREGS funds was not. Research conducted in 2008 indicated that gatekeepers in Raichur were appropriating even more public resources than they were in Dharwad (Pattenden ,b). Spending on GP seats had risen faster and further in Raichur than Dharwad – doubling in the latter between the last two GP elections, but quadrupling in the former .…”
Section: Class Conflict In Raichurmentioning
confidence: 99%
See 2 more Smart Citations